PENYUSUNAN PETUNJUK TEKNIS PENILAIAN INOVATIVE GOVERNMENT AWARD (IGA) TAHUN 2017 (DEVELOPMENT OF TECHNICAL INSTRUCTIONS INOVATIVE GOVERNMENT AWARD (IGA) ASSESSMENT 2017) - Ray Septianis Kartika (Inovasi, 2018)
Agency for Research and Development (BPP) Ministry of Home Affairs carries out the mandate of PP NO.38 Year 2017 on regional innovation to reward innovative regions through the IGA. In the implementation, BPP Kemendagri did not have the technical guidelines to conduct an IGA assessment. Therefore, the problem of this study is (1) the lack of explanation of governance indicators, public services and other innovations, (2) unclear selection mechanism of participants and (3) no explanation of the winner determination pattern relevant to PP NO.38 year 2017 (1) make indicators of governance innovation assessment, public service and other innovations, (2) develop participant selection mechanisms, and (3) establish winning patterns. The study method is desk study through qualitative approach. Based on interviews, Focuss Group Discussion (FGD), and the results of the study in the Year 2016 on local innovation strategies presented descriptively. The results of this study are Firstly, the indicators of public service, governance and other local innovations seen from the utilization, authority, novelty, replication, charging the cost and quantity of innovation area. Second, the selection mechanism through administrative selection, profile and presentation verification. The three determinations of winners are based on factual validation. The suggestion is that this instrument can be tested by the instrument on the prepared indicators and need an intensive monev to the nominees. Based on that, then this guidance as a handle to implement a better IGA in the future. Keywords: regional innovation, local government, assesment, IGA